The application of precautionary principle under the SPS agreement by the WTO DSS: an analytical appraisal - Ansari, Abdul Haseeb; Wartini, Sri (The Indian Society of International Law, 2013)
Abstract Those who develop genetically modified organisms want to market it in the country invention, where it is developed, and export them for monetary gain. The ethical aspect of such inventions and innovations strives for not venturing into them if their introduction may impair human, animal and plant life and health or adversely affect the environment. Inventors and innovators must give priority to biosafety. It is for this reason that the concept of precautionary principle has been developed and enforced through international and national laws. The SPS Agreement and the Cartagena Protocol are there to ensure biosafety, but they serve different purposes, i.e. international trade and protection of the environment. The precautionary provision contained in the Cartagena Protocol is in in line with the conservation imperatives of the Convention of Biological Diversity. But the irony is that the dispute settlement body, e.g. the Panels and the Appellate Body have given effect to the SPS Agreement. The paper critically examines the decisions given by WTO Dispute Settlement System (DSS) and subscribes to the view that DSB should determine the scope of precautionary principle in line with the Cartagena Protocol.